Pengaruh Customer Experience, Customer Trust Dan Customer Value Terhadap Customer Loyalty (Studi Kasus Pada Pelanggan Wizzmie Cabang Tlogomas ) - Alfarisi, M; Basalamah, Muhammad Ridwan; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine the impact of customer experience, customer trust, and customer value on the loyalty of Wizzmie customers at the Tlogomas branch in Malang. A quantitative research method was employed, utilizing primary data collected from respondents' answers through questionnaires distributed to Wizzmie customers at the Tlogomas branch. The study's population consists of all Wizzmie customers at this branch. The sampling method used was purposive sampling, resulting in 80 samples being selected for testing, with sample size measurement conducted using a Likert scale. The analysis results indicate that customer experience influences customer loyalty, customer trust affects customer loyalty, and customer value also has an impact on customer loyalty among Wizzmie customers at the Tlogomas branch in Malang. Keywords: Customer Experience, Customer Trust, Customer Value, Customer Loyalty